ANALISIS RISIKO PORTOFOLIO KREDIT OBLIGASI KORPORASI MENGGUNAKAN METODE CREDITMETRICS - PRATINI, I GUSTI MADE AYU ANGGUN TIARA; DHARMAWAN, KOMANG; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika, 2024)
Bond is a medium or long-term debt agreement which when the bond matures will be paid back with the interest. Bonds are issued to obtain new fund flows to meet operational needs and strengthen financial position.  One of the risks of bonds is credit risk. This risk occurs due to the issuer's inability to continue and complete its obligations. This risk often occurs in corporate bonds. So, investors need to conduct risk analysis and proper risk management. One method of credit risk analysis is the creditmetrics. In this method, credit score changes are not only caused by the probability of default, but also caused by migration of company ratings. This study aims to calculate the portfolio risk of six corporate bonds and determine the weight that must be given to each bond, so that the minimum risk will be obtained. The estimated portfolio risk obtained is Rp. 15.615 billion with an average portfolio value is Rp. 18.74 billion. Then the weight that must be given to each bond is the first bond of -1.308%, the second bond is -8.542%, the third bond is 32.798%, the fourth bond is 77.716%, the fifth bond is -1.982%, and the sixth bond is 1.317%.